Advances in Surface Design and Biomedical Applications of Magnetic Nanoparticles - Casagrande-Denardin, J (Elsevier B.V., 2024)
Despite significant efforts by scientists in the development of advanced nanotechnology materials for smart diagnosis devices and drug delivery systems, the success of clinical trials remains largely elusive. In order to address this biomedical challenge, magnetic nanoparticles (MNPs) have gained attention as a promising candidate due to their theranostic properties, which allow the simultaneous treatment and diagnosis of a disease. Moreover, MNPs have advantageous characteristics such as a larger surface area, high surface-to-volume ratio, enhanced mobility, mass transference and, more notably, easy manipulation under external magnetic fields. Besides, certain magnetic particle types based on the magnetite (Fe3O4) phase have already been FDA-approved, demonstrating biocompatible and low toxicity. Typically, surface modification and/or functional group conjugation are required to prevent oxidation and particle aggregation. A wide range of inorganic and organic molecules have been utilized to coat the surface of MNPs, including surfactants, antibodies, synthetic and natural polymers, silica, metals, and various other substances. Furthermore, various strategies have been developed for the synthesis and surface functionalization of MNPs to enhance their colloidal stability, biocompatibility, good response to an external magnetic field, etc. Both uncoated MNPs and those coated with inorganic and organic compounds exhibit versatility, making them suitable for a range of applications such as drug delivery systems (DDS), magnetic hyperthermia, fluorescent biological labels, biodetection and magnetic resonance imaging (MRI). Thus, this review provides an update of recently published MNPs works, providing a current discussion regarding their strategies of synthesis and surface modifications, biomedical applications, and perspectives. © 2024 Elsevier B.V.